Upaya Peningkatan Wawasan Peternak Kambing Perah Peranakan Etawa Kelompok Ternak “Ngudi Rejeki” di Desa Jarak - Dhian Satria Yudha Kartika; Layra Cholifah Lordly Resolute; Muhammad Hilman Zafiri; Ririn Oktavita Sari; Viona Nadestri (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
The "Ngudi Rejeki" Livestock Group is a group of Etawa breed dairy goats located in the Desa Jarak. The livestock group focuses on improving the quality of milk production for Etawa breed dairy goats. However, there are several problems experienced by livestock groups in achieving this, where the lack of knowledge possessed by breeders is one of the main problems. The use of the PRA method aims to consider potential partners. The implementation of this program involves the participation of livestock groups which are analyzed using a qualitative descriptive method through several stages, namely discussion sessions carried out through Focus Group Discussion (FGD) activities, consultation and counseling, transfer of appropriate technology, mentoring and guidance. The program carried out has had a positive impact in terms of increasing the knowledge of the "Ngudi Rejeki" Livestock Group regarding the maintenance of Etawa breed dairy goats so they are able to produce good quality goat milk.